IMPLEMENTATION OF PUBLIC CONTROL OF MEDIA IN UZBEKISTAN AND ITS SPECIFIC FEATURES - Xurshida Hasanova (Scholar Express Journals, 2023)
Currently, public control is of great importance in the effective functioning of state administration and authorities. The sphere of influence of this institute is extremely high in that the leaders and employees of state bodies strictly follow the laws and fulfill their duties and obligations responsibly. From this point of view, in the implementation of public control, first of all, the role of all citizens, as well as non-governmental organizations and mass media, should be strengthened. In this regard, the sense of responsibility, initiative, involvement in the political, socio-economic processes taking place in Uzbekistan should be formed in the mind of every person. If we are intolerant of any violations of the law, if we evaluate the actions of officials as a majority, if we freely express our opinions, then the rule of law will be truly ensured. Due to the results of pragmatic, open and transparent new stage reforms implemented in Uzbekistan in recent years, the influence of public control in our society has significantly increased. Everyone sees and knows that many shortcomings and problems, cases of violations of the law are put an end to, especially in social networks and mass media. In this article, current issues related to the implementation of public control of mass media in Uzbekistan are scientifically and creatively studied and covered on a scientific and analytical basis
Keywords: public control; citizen; social networks